Towards the understanding of engagement in digital signage advertising - Wong, Steven Sue Hong (2022)
The implementation of digital advertising has brought numerous advantages to the marketers who compete to reach their customers to improve sales and traffic. Digital signage, a digital screen that displays distinct types of content has become one of the forms of digital advertising. Digital signage aims to attract the audience to view it and at the same time deliver intended messages to them to turn them into potential buyers of a particular product or service. Therefore, measuring the effectiveness of the digital signage or the advertisements played through digital signage is paramount to helping advertisers profile their customers. One of the approaches to measure advertising effectiveness is through engagement from the target audience. However, in the context of digital signage, academic literature has been scarce and this study intends to shed light on how engagement works on digital signage advertising. With that said, this study devises an engagement framework to elucidate the audience engagement process in the context of digital signage advertising. To measure audience engagement, this study constructs a set of measurement scales to gauge the engagement of the advertisement audience empirically through various data analysis tests. Furthermore, the computer vision technique is incorporated into the study to capture the audience data such as their dwell time. The audience dwell time is utilised as the main metric to gauge the estimated engagement levels of the audience to produce various customer profiles depending on the engagement levels. The results obtained from statistical analyses indicate that different dwell time groups impact the audience engagement levels, thus serve as a viable indicator of gauging engagement. The findings from the survey suggest that the proposed Digital Signage Engagement (DiSE) framework plays an important role to test the advertising effectiveness of digital signage advertising. This provides valuable information for advertisers to have better advertising strategies and the audience can be more engaged to the advertisements. However, the proposed framework can be further tested in other advertising platforms and more advanced computer vision techniques such as gaze tracking can be utilised to capture audience dwell time more accurately.